Answer: X = y - yi - 7i
Y = (x + 7i)/(1 - i)
Step-by-step explanation: for the case of (X) you only need to pass the 7i to the other side with the subtraction sign (-7i), then we get this equation:
x + 7i = y − yi
X = y - yi - 7i
in the case of the (Y), first we select the common multiple.
y - yi = y(1 - i)
if we replace it in the original expression, we get the following equation:
x + 7i = y(1 - i)
after that you can pass the value (1 - i) to the other side dividing,
Y = (x + 7i)/(1 - i)
In step 2 .. because when you multiple by -4 in step 1 , the equation in step 2 will be ( -4y =-16 + 8z)
-20 because 40 is a positive and spent is negative
I believe it 9/20
hope that helped!!!
:)
if its not give the multiple answer choice if it has one!<span />
Answer:
60.75
Step-by-step explanation:
sinA sinB
------- = -----
a b
sin(79)/9 = sinB/8
inverse sin B = 0.87
B = 60.75